Pengaruh Leverage, Likuidity, Firm Size, Dan Investment Opportunity Set Terhadap Earning Quality - Eka Noviyanti; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims at how the influence of leverage, liquidity, company size and investment opportunity set on earnings quality in manufacturing industries listed on the Indonesia Stock Exchange during 2017 - 2019. Sample was selected using purposive sampling method and the valid data was 76 companies. Data processing techniques using dated panel what helped by Eviews program and Microsoft Excel 2013. The results of this study indicate that leverage and firm size have a significant influence on earning quality, and liquidity and investment opportunity set don’t have a significant influence on earning quality.The implication of this study is the need to increase the accuracy of leverage, liquidity, firm size and investment opportunity set to increase earning quality of company in order to predict future cash flows and become an accurate basis for users of financial statements that make financial reports the basis for decision making.